Neuropeptide Y (NPY) - (:unkn) unknown (My University, 1994)
Along with its inherent vasoconstrictor properties, neuropeptide Y (NPY) potentiates the effects of vasoactive catecholamines as well as other pressor substances. It influences the secretion of hormones known to participate in body fluid and blood pressure. It is a neuroregulator effecting the cardiovascular system. Its effects on food intake and various hormone secretions could prove to be therapeutically useful.